Monkey Trouble : the Scandal of Posthumanism. - Peterson, Christopher (Knowledge Unlatched Select 2017 (on order), 2017)
Monkey Trouble explores the turn toward immanence in contemporary posthumanism, which aims to extend hospitality to animals, plants, and even insentient things. This book argues that the displacement of anthropocentrism must cultivate a human/nonhuman relationality that affirms the immanent transcendency spawned by our phantasmatic humanness.